CONSIDERATIONS ABOUT VOLUNTEERING AND ITS IMPORTANCE - Sergiu-Octavian David (Agora International Journal of Economical Sciences (AIJES), 2024)
Volunteering, as defined, is an activity carried out voluntarily by anindividual, without expecting directly or implicitly a financial reward or goods. It plays animportant role in democratic societies, often being a form of social inclusion and integration,contributing to the development and implementation of state policies, and being an instrumentfor promoting social cohesion. "Volunteering is the best example of democracy. We vote inelections, but when you volunteer, you vote every day for the community in which you want tolive." Marjorie Moore
Keywords: 330